Pengaruh Pemberian Ikan Rucah dengan Waktu yang Berbeda Terhadap Kepiting Bakau (Scylla serrata) dalam Media Keranjang - Murtada, Akmal; Yusapri, Andi; Rachman. B, Arief (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2024)
Research on the effect of giving trash fish at different times to mangrove crabs (Scylla serrata) in fruit basket media was carried out from October to December 2023. This research was carried out in Sapat Village, Kuala Indragiri District. The aim of this research was to determine the growth of mangrove crabs using the dry method in fruit baskets by feeding them at different times, namely morning, afternoon and evening. The results of the research showed that the average growth of Mangrove Crabs at breakfast time was 2,0 gr, the average growth of Mangrove Crabs at lunch time was 1.6 gr, the average growth of Mangrove Crabs at dinner time days amounting to 4,4 gr. The most effective growth is when feeding at night, while growth in the morning and afternoon of crab weight is less effective because crabs are more active at night. In the dry method, crabs experience moulting ± 60 days later than the aeration method.